Recovery of quarries with autochthonous vegetal species at Arrábida Natural Park - Rodrigues, Fátima (2010)
To aid in the of environmental and landscape recovery quarries integrated in the Arrábida Natural Park (PNA) a contract involving official Portuguese entities was celebrated since 1998 to produce autochthonous plants. This contract was supported by the project “Valorisation of waste heat from Setúbal Power Plant in protected cultivation” that had the main goal to demonstrate the practical application of low temperature waste heat from power plant in greenhouses environmental conditioning. The contract was developed in partnership with EDP the major Portuguese energy operator as leadership, LNEG as scientific coordinator, PNA as technical partner and the municipalities of Setúbal and Palmela as institutional partners. The production of thousands of autochthonous plants have been cultivated in greenhouses equipped with heating systems allowing the circulation of low-temperature effluent waste heat were resulting plants with adapted characteristics that increased their adaptability to adverse environments. Located on the Setúbal Peninsula (Portugal west coast) the Arrábida Natural Park was created on 1976 and represents a place of special interest in the panorama of national protected area with protected natural, cultural and landscape values and promoting the economical development and the life quality of the resident populations. Its scientific value and state of conservation has led to this protected area being included in the European Network of Biogenetic Reserves. This Natural Park encloses some coastal mountains and Sado estuary that constitute a paradise not only for lovers of Nature, but also as an inexhaustible source of joy for geologists and biologists. The climate is temperate and illustrates its features more Mediterranean. Associated human activities as fishery, agricultural and mineral activities easily justify the special attention given to the preservation of this protected environment. There are 11 licensed quarries dated before the creation of the PNA subjected to environmental and landscape recovery plans according to national laws that obliged topographical regularization with inert wastes from their extractive activities and the ecological restoration implemented with autochthonous species. Currently, legal protection and management plan for the PNA prohibits the expansion of existing quarries and the beginning of new.